Seasonal variation in expression pattern of heat shock factor genes in Ovis aries and Capra hircus - LATIKA JAISWAL; SACHINANDAN DE; RAVI KANT SINGH (Indian Journal of Animal Sciences, 2019)
In many dairy animals the correlation between longevity and stress resistance has been observed, which suggests that, for the regulation of lifespan, the ability to sense and respond to environmental challenges is important. Therefore it is necessary to observe the role of heat shock factors (HSFs), in the regulation of longevity which acts as a master transcriptional regulator of stress-inducible gene expression and protein folding homeostasis. Exposure to heat stress causes changes which have a substantial impact on production and productivity. Therefore the four major mammalian HSF genes, HSF-1, 2, 4, and 5 have been studied in sheep and goat. Major objective of this study was to analyze the expression status of these genes in sheep and goat using gene-specific primers. Changes in the gene expression profile of these two species were noted by quantitative real-time PCR (qRT-PCR). The expression level in both the species has been studied and it was found that the level of HSF-1, 2, 4 and 5 mRNA was higher in testis compared to all the tissues examined. Moreover, they are expressed in a wide range of tissues but their expression was variable. The analysis of seasonal changes in blood profile in goat and sheep showed an up-regulation in HSF-4 and HSF-5 genes in winter. The study implicates that the intricate balance of different HSFs is adjusted to minimize the effect of seasonal changes in environmental conditions. These findings enlighten our understanding of the complex, context-dependent regulation of HSF gene expression under normal and stressful conditions.